42.4k views
3 votes
Solve the equation below and place the answer in the answer box. Show all steps in your solution.

4(x-3)+2x=3(x+5)

User Tfv
by
5.2k points

2 Answers

3 votes

Answer:

X=9

Explanation:

Open the brackets

4x - 12 + 2x = 3x + 15

Collect like terms

4x+2x-3x= 15+12

3x=27

Divide both sides by the coefficient of x which is 3

3x/3 = 27/3

x= 9

User Norfeldt
by
5.9k points
3 votes

Answer: x = 9

Explanation:

Let's solve your equation step-by-step.

4(x−3)+2x=3(x+5)

Step 1: Simplify both sides of the equation.

4(x−3)+2x=3(x+5)

(4)(x)+(4)(−3)+2x=(3)(x)+(3)(5)(Distribute)

4x+−12+2x=3x+15

(4x+2x)+(−12)=3x+15(Combine Like Terms)

6x+−12=3x+15

6x−12=3x+15

Step 2: Subtract 3x from both sides.

6x−12−3x=3x+15−3x

3x−12=15

Step 3: Add 12 to both sides.

3x−12+12=15+12

3x=27

Step 4: Divide both sides by 3.

3x

3

=

27

3

x=9

Answer:x=9

copy and paste this and it will be correct.

User Tukusejssirs
by
5.3k points